Horizontal mergers between multisided platforms: insights from cournot competition - Correia-da-Silva, Joao (2020)
This paper discusses the literature on horizontal mergers between multisided platforms and argues that the Cournot model can provide useful insights into the welfare effects of such mergers. To illustrate those insights, we develop a simple model in which two‐sided platforms offer a homogeneous service and compete à la Cournot, and derive the effects of “average‐marginal‐cost‐preserving” mergers on consumers on both sides of the market. We conclude with a discussion of several research avenues that could be explored to understand better the impact of horizontal mergers between multisided platforms.